LANDCOVER VARIATION AND IMPLICATION FOR BASEFLOW VALUE AT UPPER CITARUM BASIN - SYAHIDAH (NIM: 22713003); Pembimbing : Prof. Ir. Lambok M. Hutasoit, Ph.D.; Dr. Rusmawan, MUHSHONATI
Variation of landcover at Upper Citarum Basin continuously can affect the condition of groundwater. Baseflow is one of the very important hydrological characteristics in a watershed system. Baseflow value at Upper Citarum Basin during 1995-2014 is calculated using separation method Recursive Digital Filter, One Parameter. Estimation of Baseflow Index (BFI) at Citarum-Nanjung river results in the average of 57%. Landcover at Upper Citarum Basin is described by Normalized Difference Vegetation Index (NDVI) and Normalized Difference built-up Index (NDBI). In this study, NDVI and NDBI are calculated using Satellite Image Landsat 5, Landsat 7 Thematic Mapper, and Landsat 8 during 1995-2014 at Upper Citarum Basin. The value of NDVI can describe the distribution of vegetation in Citarum Hulu, while NDBI can not describe the landcover well. Linear regression is used to obtain the relationship between baseflow with rainfall, NDVI, and surface geology. Correlation between rainfall and baseflow in dry season is 0.5. In wet season, correlation between baseflow and rainfall and NDVI is 0.7. Addition of surface geological elements increases the value of the correlation to become 0.73.